TOPCon battery capable of reducing UV attenuation and preparation method thereof

By using three silicon nitride layer/two silicon nitride layer/one silicon oxide layer as the front anti-reflection layer in TOPCon solar cells, Si-H bond fracture caused by UV exposure is solved by combining with the back silicon nitride layer. The problem is that the photoelectric conversion efficiency and UV tolerance of the battery are improved.

CN119230622AInactive Publication Date: 2024-12-31HUAIAN JIETAI NEW ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411345301.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

TOPCon solar cells break Si-H bonds under UV exposure, the hydrogen content decreases, and the void density increases, resulting in surface passivation and deterioration, affecting battery efficiency.

Method used

By adjusting the front coating process, three silicon nitride layers/two silicon nitride layers/one silicon oxide layer are used as the front anti-reflection layer, and three silicon nitride layers on the back are combined to form a passivation layer to reduce UV attenuation.

Benefits of technology

It effectively reduces the reflectivity and dark current of light, improves the open circuit voltage and photoelectric conversion efficiency, and enhances the battery's tolerance to UV.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230622A_ABST
    Figure CN119230622A_ABST
Patent Text Reader

Abstract

The invention discloses a TOPCon battery capable of reducing UV attenuation and a preparation method thereof, and belongs to the field of TOPCon batteries, the TOPCon battery comprises a silicon substrate, and three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer are sequentially deposited on the front surface of the treated silicon substrate to form a front surface antireflection layer; and depositing three silicon nitride layers on the back of the silicon substrate to form a back antireflection layer. The polycrystalline solar cell has the advantages that three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer are arranged on the front face of the silicon substrate to serve as the front face antireflection layer, the color stability is high, the surface of the silicon substrate can be better passivated, light reflection can be better reduced, the open-circuit voltage and the short-circuit current of the polycrystalline solar cell are improved, and the service life of the polycrystalline solar cell is prolonged. Therefore, the photoelectric conversion efficiency of the polycrystalline solar cell is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of TOPCon cells, and in particular to a TOPCon cell capable of reducing UV attenuation and a preparation method thereof. Background Art

[0002] In recent years, high-efficiency and low-cost solar cells have been one of the research hotspots in the photovoltaic industry. TOPCon solar cells are made by first preparing a 1-2nm tunneling oxide layer on the back of the cell, and then depositing a layer of doped polysilicon. The two together form a passivation contact structure, providing good interface passivation for the back of the silicon wafer. However, with the promotion of TOPCon cells, UV attenuation has become another hot topic in the photovoltaic cell industry.

[0003] UV exposure will cause the Si-H bonds in TOPCon solar cells to break, the hydrogen content to drop significantly, and the void density to increase, thereby introducing more defects on the surface, causing surface passivation degradation, and thus causing component attenuation. At present, under the premise of pursuing high reliability of components, some users choose to start with component-side packaging materials, such as film, glass, etc., but this is not cost-friendly for components. In response to this problem, the present invention improves the UV attenuation problem by adjusting the front coating process.

[0004] In view of this, the inventor conducted in-depth research on this demand, and thus the present case was produced. Summary of the invention

[0005] In order to solve the problem in the prior art that UV exposure of TOPCon cells causes Si-H bonds to break, hydrogen content to drop significantly, void density to increase, and more defects to be introduced on the surface, resulting in surface passivation degradation, the present invention provides a method for preparing a TOPCon cell with reduced UV attenuation, comprising the following steps:

[0006] Step 1: Clean and texturize the silicon substrate, diffuse boron on the front side, and perform etching and alkaline polishing treatment in sequence;

[0007] Step 2, using LPCVD process to prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the treated silicon substrate;

[0008] Step 3, using POCl3 as a diffusion source, performing back side phosphorus diffusion to form a doped polysilicon layer;

[0009] Step 4: RCA is used to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove the PSG, and remove the edge and front PSG;

[0010] Step 5, performing aluminum oxide atomic layer deposition on the front side of the silicon substrate to form an aluminum oxide passivation layer;

[0011] Step 6: depositing three silicon nitride layers, two silicon oxynitride layers, and one silicon oxide layer on the front side of the silicon substrate in sequence to form a front anti-reflection layer;

[0012] Step 7, depositing three silicon nitride layers on the back side of the silicon substrate to form a back side anti-reflection layer;

[0013] Step eight, screen printing, electrode printing and high-temperature sintering are performed on the front and back sides in sequence to form good ohmic contact and obtain front metal electrodes and back metal electrodes.

[0014] Preferably, in step six, three silicon nitride layers are deposited on the front side, using a tubular plasma vapor deposition machine, and after the sheet is placed on a graphite boat, it is sent to a furnace tube by a paddle, evacuated, and annealed at a temperature of 540-580°C for 1600-2000s; the furnace tube is drained under a continuous vacuum breaking / vacuuming state, and when the temperature is stabilized at 540-580°C, SiH4 and NH3 are introduced at a flow rate of 2000-3000sccm / min and 9000-10000sccm / min, respectively, at a radio frequency power of 12-18kw. , the reaction time is 120-180s, and the first silicon nitride layer is deposited; then SiH4 and NH3 are introduced with flow rates of 1600-2000sccm / min and 11000-14000sccm / min respectively, and the reaction time is 120-180s, and the second silicon nitride layer is deposited; finally, SiH4 and NH3 are introduced with flow rates of 1000-1500sccm / min and 10000-15000sccm / min respectively, and the reaction time is 220-280s, and the third silicon nitride layer is deposited.

[0015] Preferably, the first silicon nitride layer has a thickness of 16 to 20 nm and a refractive index of 2.10 to 2.30%;

[0016] The second silicon nitride layer has a thickness of 14 to 18 nm and a refractive index of 2.00 to 2.07%;

[0017] The third silicon nitride layer has a thickness of 18 to 22 nm and a refractive index of 1.80 to 2.00%.

[0018] Preferably, in step 6, two layers of silicon nitride oxide are deposited on the front side, and under the condition of depositing three layers of silicon nitride, the flow ratios are sequentially

[0019] The reaction gases are SiH4:NH3:N2O=(1000-1100):(4000-5000):(6000-7000)sccm / min and SiH4:NH3:N2O=(800-900):(3000-4000):(8000-9000)sccm / min. Under a radio frequency power of 12-18kw, the film formation time is 110-130s for both times, and two layers of silicon nitride oxide film with a thickness of 5-9nm are deposited on the surface of the battery in sequence.

[0020] Preferably, in the step six, a layer of silicon oxide is deposited on the front side, and under the condition of depositing two layers of silicon nitride oxide layers, a reaction gas with a flow ratio of NH3:N2O=(800-1000):(10000-13000)sccm / min is introduced, and at a radio frequency power of 12-18kw, a layer of silicon oxide film with a refractive index of 1.5-1.9% and a film thickness of 4-6mm is deposited on the surface of the battery, and the reaction time is 80-100s.

[0021] Preferably, in the step seven, three layers of silicon nitride are deposited on the back, using a tubular plasma vapor deposition machine, and after the graphite boat is placed, the sheet is sent to the furnace tube by a paddle, evacuated, and annealed at a temperature of 500-550°C for 800-1000s; the furnace tube is leaked under continuous vacuum breaking / vacuuming, the reaction temperature is 500-550°C, the RF power of the first film is 11-15kw, and the flow ratio of the reaction gas introduced is SiH4:NH3=(2000-3000):(9000-10000)sccm / min, the reaction time is 100-160s, and a first silicon nitride layer with a refractive index of 2.1-2.5% and a film thickness of 18-20mm is deposited on the surface of the battery; the RF power of the second film is The RF power of the third film is 14-16kw, the flow ratio of the reaction gas introduced is SiH4:NH3=(1000-2000):(12000-13000)sccm / min, the reaction time is 160-200s, and a second silicon nitride layer with a refractive index of 2.0-2.2% and a film thickness of 20-24mm is deposited on the surface of the battery; the RF power of the third film is 14-16kw, the flow ratio of the reaction gas introduced is SiH4:NH3=(1300-1500):(13000-15000)sccm / min, the reaction time is 200-260s, and a third silicon nitride layer with a refractive index of 1.8-2.0% and a film thickness of 18-20mm is deposited on the surface of the battery.

[0022] Preferably, in the step five, an aluminum oxide passivation layer is deposited on the front side, using a chamber-type vapor phase molecular deposition machine. Through a manipulator, the silicon wafer is lowered into the groove of the aluminum boat, and a paddle is inserted to place it in a furnace tube. After the furnace door is closed, a dry pump is turned on to evacuate the chamber. When the temperature in the chamber is 220-280°C, water vapor at 40-50°C is introduced for 10-12s to form a hydroxyl layer on the front surface of the silicon body. After nitrogen is purged for 8-12s, tribasic aluminum vapor at 40-50°C is introduced, and nitrogen is purged for 8-12s. The above cycle is repeated 34-36 times to form an aluminum oxide passivation layer of 5-7nm on the front surface.

[0023] Preferably, in step one, the silicon substrate is subjected to double-sided texturing treatment to obtain a textured silicon wafer, and then boron ions are diffused on the front side of the textured silicon wafer to form the P+ doped layer and the borosilicate glass layer, and then the borosilicate glass layer is removed by etching, and the back surface of the crystalline silicon substrate is polished by alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process.

[0024] Preferably, in step 4, RCA is used to clean the back oxide layer, the N+ layer generated on the front and the edge during phosphorus diffusion, and remove the front borosilicate glass layer and the front phosphosilicate glass layer.

[0025] The present invention also provides a TOPCon solar cell obtained by adopting the above preparation method.

[0026] Preferably, it comprises a silicon wafer, wherein a P+ diffusion layer, an aluminum oxide passivation layer, a front anti-reflection layer and a front metal electrode are sequentially arranged on the front side of the silicon wafer, and a tunneling oxide layer, a doped polysilicon layer, a back anti-reflection layer and a back metal electrode are sequentially arranged on the back side; the front metal electrode penetrates the front anti-reflection layer and the aluminum oxide passivation layer to form an ohmic contact with the P+ diffusion layer; the back metal electrode penetrates the back anti-reflection layer to form an ohmic contact with the doped polysilicon layer.

[0027] Preferably, the front anti-reflection layer is three layers of silicon nitride layers / two layers of silicon oxynitride layers / one layer of silicon oxide; and the back anti-reflection layer is three layers of silicon nitride layers on the back.

[0028] The beneficial effects produced by the technical solution of the present invention are as follows:

[0029] (1) The present invention reduces the reflected light to less than 15% by setting three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer as the front anti-reflection layer on the front of the silicon substrate, and has high color stability, which can better passivate the surface of the silicon substrate and reduce the reflection of light, thereby improving the open circuit voltage and short circuit current of the polycrystalline solar cell, thereby effectively improving the photoelectric conversion efficiency of the polycrystalline solar cell. In addition, it can also greatly improve the utilization rate of solar light by the cell, help to increase the photocurrent density, and then improve the conversion efficiency. At the same time, the passivation of the surface of the cell by hydrogen in the film reduces the surface recombination rate of the emitter junction, reduces the dark current, increases the open circuit voltage, and improves the photoelectric conversion efficiency.

[0030] (2) Since the refractive index of silicon nitride is basically between 2.00-2.40, the loss of light after reaching the surface is still more than 18%. At this time, the introduction of a silicon oxide film with a refractive index of 1.5-1.9% can greatly reduce the light reflectivity. However, there are no H atoms in the silicon oxide film, which leads to a decrease in the passivation ability. Therefore, two layers of silicon oxynitride are introduced in the middle film thickness. During the process, high-temperature instantaneous annealing will break off free H ions, further enhancing the passivation effect on the battery. Therefore, the present invention sets three layers of silicon nitride / two layers of silicon oxynitride / one layer of silicon oxide as the front anti-reflection layer, which can reduce H injection, reduce H enrichment, and reduce losses caused by H recombination, so that the UV attenuation of the TOPCon battery is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 It is a schematic diagram of the structure of the TOPCon solar cell in the present invention.

[0033] In the figure, 1. silicon substrate; 2. P+ diffusion layer; 3. aluminum oxide passivation layer; 4. front anti-reflection layer; 5. front metal electrode; 6. tunneling oxide layer; 7. doped polysilicon layer; 8. back anti-reflection layer; 9. back metal electrode. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] This embodiment uses three layers of silicon nitride / two layers of silicon oxynitride / one layer of silicon oxide as the front anti-reflection layer on the TOPCon solar cell, which can reduce H injection, reduce H enrichment, and reduce the loss caused by H recombination, so that the UV attenuation of the TOPCon cell is greatly improved, and finally the efficiency of the TOPCon cell is greatly improved. The specific implementation is as follows:

[0036] like Figure 1 As shown, a method for preparing a TOPCon cell with reduced UV attenuation comprises the following steps:

[0037] Step 1: Perform double-sided texturing on a silicon substrate 1 to obtain a textured silicon wafer, then perform boron ion diffusion on the front side of the textured silicon wafer to form a P+ doped layer 2 and the borosilicate glass layer, then remove the borosilicate glass layer by etching, and polish the back surface of the silicon substrate 1 by alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process;

[0038] Step 2: using LPCVD process to prepare a tunnel oxide layer 6 and an intrinsic polysilicon layer on the back side of the processed silicon substrate 1;

[0039] Step 3, using POCl3 as a diffusion source, performing back side phosphorus diffusion to form a doped polysilicon layer 7;

[0040] Step 4: RCA is used to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove the PSG, and remove the edge and front PSG;

[0041] Step 5, performing aluminum oxide atomic layer deposition on the front surface of the silicon substrate 1 to form an aluminum oxide passivation layer 3;

[0042] Step 6: depositing three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer on the front surface of the silicon substrate 1 in sequence to form a front anti-reflection layer 4;

[0043] Step 7, depositing three silicon nitride layers on the back side of the silicon substrate 1 to form a back side anti-reflection layer 8;

[0044] Step eight, screen printing and electrode printing are sequentially performed on the front and back sides of the silicon substrate 1 and then sintered at high temperature to form a good ohmic contact, thereby obtaining a front metal electrode 5 and a back metal electrode 9.

[0045] As a preferred embodiment, in the step six, three layers of silicon nitride are deposited on the front side, and a tubular plasma vapor deposition machine is used. After the graphite boat is placed, the sheet is sent to the furnace tube by a paddle, and vacuumized. The furnace tube is annealed at a temperature of 540-580°C for 1600-2000s; the furnace tube is leaked under a continuous vacuum breaking / vacuuming state, and when the temperature is stabilized at 540-580°C, SiH4 and NH3 are introduced at a flow rate of 2000-3000sccm / min and 9000-10000sccm / min, respectively, at a radio frequency power of 12-18kw, and the reaction time is 120-180s to deposit the first silicon nitride layer; SiH4 and NH3 are introduced at a flow rate of 2000-3000sccm / min and 9000-10000sccm / min, respectively, and the reaction time is 120-180s.

[0046] The second silicon nitride layer is deposited at 1600-2000sccm / min and 11000-14000sccm / min, with a reaction time of 120-180s respectively; finally, SiH4 and NH3 are introduced at a flow rate of 1000-1500sccm / min and 10000-15000sccm / min, with a reaction time of 220-280s, to deposit the third silicon nitride layer.

[0047] As a preferred embodiment, the first silicon nitride layer has a thickness of 16 to 20 nm and a refractive index of 2.10 to 2.30%; the second silicon nitride layer has a thickness of 14 to 18 nm and a refractive index of 2.00 to 2.07%; and the third silicon nitride layer has a thickness of 18 to 22 nm and a refractive index of 1.80 to 2.00%.

[0048] As a preferred embodiment, in step 6, two layers of silicon nitride oxide are deposited on the front side, and under the condition of depositing three layers of silicon nitride, the flow ratios are sequentially

[0049] The reaction gases are SiH4:NH3:N2O=(1000-1100):(4000-5000):(6000-7000)sccm / min and SiH4:NH3:N2O=(800-900):(3000-4000):(8000-9000)sccm / min. Under a radio frequency power of 12-18kw, the film formation time is 110-130s for both times, and two layers of silicon nitride oxide film with a thickness of 5-9nm are deposited on the surface of the battery in sequence.

[0050] As a preferred embodiment, in step 6, a silicon oxide layer is deposited on the front side, and under the condition of depositing two silicon oxynitride layers, the flow rate ratio is

[0051] NH3:N2O=(800-1000):(10000-13000)sccm / min of reaction gas, under 12-18kw RF power, a layer of silicon oxide film with a refractive index of 1.5-1.9% and a film thickness of 4-6mm is deposited on the surface of the battery, and the reaction time is 80-100s.

[0052] As a preferred embodiment, in the step seven, three layers of silicon nitride are deposited on the back, and a tubular plasma vapor deposition machine is used. After the sheet is placed on the graphite boat, it is sent to the furnace tube by a paddle, evacuated, and annealed at a temperature of 500-550°C for 800-1000s; the furnace tube is leaked under continuous vacuum breaking / vacuuming, the reaction temperature is 500-550°C, the RF power of the first film is 11-15kw, and the flow ratio of the reaction gas is SiH4:NH3=(2000-3000):(9000-10000)sccm / min, the reaction time is 100-160s, and a first silicon nitride layer with a refractive index of 2.1-2.5% and a film thickness of 18-20mm is deposited on the surface of the battery; the second film is sprayed The RF power is 14-16kw, the flow ratio of the reaction gas introduced is SiH4:NH3=(1000~2000):(12000~13000)sccm / min, the reaction time is 160~200s, and a second silicon nitride layer with a refractive index of 2.0~2.2% and a film thickness of 20~24mm is deposited on the surface of the battery; the RF power of the third film is 14-16kw, the flow ratio of the reaction gas introduced is SiH4:NH3=(1300~1500):(13000~15000)sccm / min, the reaction time is 200~260s, and a third silicon nitride layer with a refractive index of 1.8~2.0% and a film thickness of 18~20mm is deposited on the surface of the battery.

[0053] As a preferred embodiment, in the step five, an aluminum oxide passivation layer is deposited on the front side, and a chamber-type vapor phase molecular deposition machine is used. Through a manipulator, a silicon wafer is lowered into the groove of an aluminum boat, and a paddle is inserted to place it in a furnace tube. After the furnace door is closed, a dry pump is turned on to evacuate the chamber. When the temperature in the chamber is 220-280°C, water vapor at 40-50°C is introduced for 10-12s to form a hydroxyl layer on the front surface of the silicon body. After nitrogen is purged for 8-12s, tribasic aluminum vapor at 40-50°C is introduced, and nitrogen is purged for 8-12s. The above cycle is repeated 34-36 times to form a 5-7nm aluminum oxide passivation layer on the front surface.

[0054] The present invention also provides a TOPCon solar cell obtained by adopting the above preparation method.

[0055] Preferably, it includes a silicon substrate 1, the front side of the silicon substrate 1 is sequentially provided with a P+ diffusion layer 2, an aluminum oxide passivation layer 3, a front anti-reflection layer 4 and a front metal electrode 5, and the back side thereof is sequentially provided with a tunneling oxide layer 6, a doped polysilicon layer 7, a back anti-reflection layer 8 and a back metal electrode 9; the front metal electrode 5 penetrates the front anti-reflection layer 4 and the aluminum oxide passivation layer 3 to form an ohmic contact with the P+ diffusion layer 2; the back metal electrode 9 penetrates the back anti-reflection layer 8 to form an ohmic contact with the doped polysilicon layer 7.

[0056] As a preferred embodiment, the front anti-reflection layer 4 is composed of three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer; and the back anti-reflection layer 8 is composed of three silicon nitride layers.

[0057] The beneficial effects of the method for preparing a TOPCon cell for reducing UV attenuation in the present invention are further reviewed through several groups of examples.

[0058] Embodiment 1:

[0059] In this embodiment, a method for preparing a TOPCon cell with reduced UV attenuation includes the following steps:

[0060] Step 1: Perform double-sided texturing on the silicon substrate to obtain a textured silicon wafer, then diffuse boron ions on the front side of the textured silicon wafer to form a P+ doped layer and the borosilicate glass layer, then remove the borosilicate glass layer by etching, and polish the back surface of the silicon substrate with alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process.

[0061] Step 2: Prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the processed silicon substrate using an LPCVD process.

[0062] Step three, using POCl3 as a diffusion source, perform back side phosphorus diffusion to form a doped polysilicon layer.

[0063] Step 4: Use RCA to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove PSG and remove the edge and front PSG.

[0064] Step five, deposit an aluminum oxide passivation layer on the front side, using a chamber-type vapor phase molecular deposition machine, with a robot arm, lower the silicon wafer into the groove of the aluminum boat, insert a paddle and place it in the furnace tube, close the furnace door and start the dry pump to evacuate, when the temperature in the chamber is 220°C, introduce 40°C water vapor for 10 seconds, form a hydroxyl layer on the front surface of the silicon body, nitrogen purge for 8 seconds, then introduce 40°C tribasic aluminum vapor, nitrogen purge for 8 seconds, repeat the above cycle 34 times, and form a 5nm aluminum oxide passivation layer on the front surface.

[0065] Step 6: Deposit three layers of silicon nitride on the front side using a tubular plasma vapor deposition machine. After placing the sheet on the graphite boat, the sheet is sent to the furnace tube by a paddle, evacuated, and annealed at a temperature of 540°C for 1600s. Pull the furnace tube under continuous vacuum / vacuuming conditions. When the temperature stabilizes at 540°C, introduce SiH4 and NH3 at a flow rate of 2000sccm / min and 9000sccm / min, respectively, at an RF power of 12kw. The reaction time is 120s to deposit the first silicon nitride layer. The film thickness of the first silicon nitride layer is 16nm, and the refractive index is 0.04477 W / m. The rate is 2.10%; then SiH4 and NH3 are introduced at flow rates of 1600sccm / min and 11000sccm / min, respectively, and the reaction time is 120s, respectively, to deposit a second silicon nitride layer, the film thickness of the second silicon nitride layer is 14nm, and the refractive index is 2.00%; finally, SiH4 and NH3 are introduced at flow rates of 1000sccm / min and 10000sccm / min, respectively, and the reaction time is 220s, to deposit a third silicon nitride layer, the film thickness of the third silicon nitride layer is 18nm, and the refractive index is 1.80%;

[0066] Two layers of silicon oxynitride were deposited on the front side. Under the condition of depositing three layers of silicon nitride, reaction gases with flow ratios of SiH4:NH3:N2O=1000:4000:6000sccm / min and SiH4:NH3:N2O=800:3000:8000sccm / min were introduced in sequence. Under the RF power of 12kw, the film formation time was 110s for both times, and two layers of silicon oxynitride with a film thickness of 5nm were deposited on the surface of the battery in sequence.

[0067] A layer of silicon oxide is deposited on the front side. Under the condition of depositing two layers of silicon oxynitride, a reaction gas with a flow ratio of NH3:N2O=800:10000sccm / min is introduced. At an RF power of 12kw, a layer of silicon oxide film with a refractive index of 1.5% and a film thickness of 4mm is deposited on the surface of the battery. The reaction time is 80s.

[0068] Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, use a tubular plasma vapor deposition machine, place the sheet on the graphite boat, and send it to the furnace tube by the paddle, evacuate, and anneal at a temperature of 500°C for 800s; pull the furnace tube out under continuous vacuum / vacuum state, the reaction temperature is 500°C, the RF power of the first film is 11kw, and the reaction gas with a flow ratio of SiH4:NH3=2000:9000sccm / min is introduced. The reaction time is 100s, and a first silicon nitride layer with a refractive index of 2.1% and a film thickness of 18mm is deposited on the surface of the battery; the second The RF power of the first film is 14kw, the flow rate ratio of the reaction gas is SiH4:NH3=1000:12000sccm / min, the reaction time is 160s, and a second silicon nitride layer with a refractive index of 2.0% and a film thickness of 20mm is deposited on the surface of the battery; the RF power of the third film is 14kw, the flow rate ratio of the reaction gas is SiH4:NH3=1300:13000sccm / min, the reaction time is 200s, and a third silicon nitride layer with a refractive index of 1.8% and a film thickness of 18mm is deposited on the surface of the battery.

[0069] Step eight, screen printing, electrode printing and high-temperature sintering are performed on the front and back sides of the silicon substrate in sequence to form a good ohmic contact and obtain a front metal electrode and a back metal electrode.

[0070] Embodiment 2:

[0071] In this embodiment, a method for preparing a TOPCon cell with reduced UV attenuation includes the following steps:

[0072] Step 1: Perform double-sided texturing on the silicon substrate to obtain a textured silicon wafer, then diffuse boron ions on the front side of the textured silicon wafer to form a P+ doped layer and the borosilicate glass layer, then remove the borosilicate glass layer by etching, and polish the back surface of the silicon substrate with alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process.

[0073] Step 2: Prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the processed silicon substrate using an LPCVD process.

[0074] Step three, using POCl3 as a diffusion source, perform back side phosphorus diffusion to form a doped polysilicon layer.

[0075] Step 4: Use RCA to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove PSG and remove the edge and front PSG.

[0076] Step five, deposit an aluminum oxide passivation layer on the front side, using a chamber-type vapor phase molecular deposition machine, with a robot arm, lower the silicon wafer into the groove of the aluminum boat, insert a paddle and place it in the furnace tube, close the furnace door and start the dry pump to evacuate, when the temperature in the chamber is 250°C, introduce 45°C water vapor for 11 seconds, form a hydroxyl layer on the front surface of the silicon body, nitrogen purge for 10 seconds, then introduce 45°C tribasic aluminum vapor, nitrogen purge for 10 seconds, repeat the above cycle 35 times, and form a 6nm aluminum oxide passivation layer on the front surface.

[0077] Step 6: deposit three layers of silicon nitride on the front side, using a tubular plasma vapor deposition machine, after the graphite boat is placed, it is sent to the furnace tube by a paddle, evacuated, and annealed at a temperature of 560°C for 1800s; the furnace tube is leaked under the continuous vacuum breaking / vacuuming state, and when the temperature is stabilized at 560°C, SiH4 and NH3 are introduced at a flow rate of 2500sccm / min and 9500sccm / min respectively at a radio frequency power of 16kw, and the reaction time is 150s to deposit the first silicon nitride layer, the film thickness of the first silicon nitride layer is 18nm, and the film thickness of the first silicon nitride layer is 18nm. The refractive index is 2.2%; then SiH4 and NH3 are introduced at flow rates of 1800sccm / min and 12600sccm / min, respectively, and the reaction time is 150s, respectively, to deposit a second silicon nitride layer, the film thickness of the second silicon nitride layer is 16nm, and the refractive index is 2.03%; finally, SiH4 and NH3 are introduced at flow rates of 1200sccm / min and 12000sccm / min, respectively, and the reaction time is 250s, to deposit a third silicon nitride layer, the film thickness of the third silicon nitride layer is 20nm, and the refractive index is 1.9%;

[0078] Two layers of silicon oxynitride were deposited on the front side. Under the condition of depositing three layers of silicon nitride, reaction gases with flow ratios of SiH4:NH3:N2O=1080:4860:6660sccm / min and SiH4:NH3:N2O=810:3600:8010sccm / min were introduced in sequence. Under the RF power of 16kw, the film formation time was 120s for both times, and two layers of silicon oxynitride films with a thickness of 7nm were deposited on the surface of the battery in sequence.

[0079] A layer of silicon oxide is deposited on the front side. Under the condition of depositing two layers of silicon nitride oxide, a reaction gas with a flow ratio of NH3:N2O=900:11700sccm / min is introduced. At an RF power of 16kw, a layer of silicon oxide film with a refractive index of 1.7% and a film thickness of 5mm is deposited on the surface of the battery. The reaction time is 90s.

[0080] Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, use a tubular plasma vapor deposition machine, after the graphite boat is placed, it is sent to the furnace tube by the paddle, evacuated, and annealed at a temperature of 520°C for 900s; the furnace tube is leaked under the continuous vacuum breaking / vacuuming state, the reaction temperature is 520°C, the RF power of the first film is 13kw, the reaction gas with a flow ratio of SiH4:NH3=2600:9400sccm / min is introduced, the reaction time is 130s, and a first silicon nitride layer with a refractive index of 2.3% and a film thickness of 19mm is deposited on the surface of the battery; the second The RF power of the first film is 15kw, the flow rate ratio of the reaction gas is SiH4:NH3=1850:12500sccm / min, the reaction time is 180s, and a second silicon nitride layer with a refractive index of 2.1% and a film thickness of 22mm is deposited on the surface of the battery; the RF power of the third film is 15kw, the flow rate ratio of the reaction gas is SiH4:NH3=1400:14000sccm / min, the reaction time is 230s, and a third silicon nitride layer with a refractive index of 1.9% and a film thickness of 19mm is deposited on the surface of the battery.

[0081] Step eight, screen printing, electrode printing and high-temperature sintering are performed on the front and back sides of the silicon substrate in sequence to form a good ohmic contact and obtain a front metal electrode and a back metal electrode.

[0082] Embodiment 3:

[0083] In this embodiment, a method for preparing a TOPCon cell with reduced UV attenuation includes the following steps:

[0084] Step 1: Perform double-sided texturing on the silicon substrate to obtain a textured silicon wafer, then diffuse boron ions on the front side of the textured silicon wafer to form a P+ doped layer and the borosilicate glass layer, then remove the borosilicate glass layer by etching, and polish the back surface of the silicon substrate with alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process.

[0085] Step 2: Prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the processed silicon substrate using an LPCVD process.

[0086] Step three, using POCl3 as a diffusion source, perform back side phosphorus diffusion to form a doped polysilicon layer.

[0087] Step 4: Use RCA to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove PSG and remove the edge and front PSG.

[0088] Step five, deposit an aluminum oxide passivation layer on the front side, using a chamber-type vapor phase molecular deposition machine, with a robot arm, lower the silicon wafer into the groove of the aluminum boat, insert a paddle and place it in the furnace tube, close the furnace door and start the dry pump to evacuate, when the temperature in the chamber is 280°C, introduce 50°C water vapor for 12 seconds, form a hydroxyl layer on the front surface of the silicon body, nitrogen purge for 12 seconds, then introduce 50°C tribasic aluminum vapor, nitrogen purge for 12 seconds, repeat the above cycle 36 times, and form a 7nm aluminum oxide passivation layer on the front surface.

[0089] Step 6: Deposit three layers of silicon nitride on the front side using a tubular plasma vapor deposition machine. After placing the sheet on the graphite boat, the sheet is sent to the furnace tube by a paddle, evacuated, and annealed at a temperature of 580°C for 2000s. Pull the furnace tube under continuous vacuum breaking / vacuuming. When the temperature is stabilized at 580°C, introduce SiH4 and NH3 at a flow rate of 3000sccm / min and 10000sccm / min respectively at an RF power of 18kw. The reaction time is 180s to deposit the first silicon nitride layer. The film thickness of the first silicon nitride layer is 20nm, and the refractive index is 0.04477 W / m. The rate is 2.30%; then SiH4 and NH3 are introduced at flow rates of 2000sccm / min and 14000sccm / min, respectively, and the reaction time is 180s, respectively, to deposit a second silicon nitride layer, the film thickness of the second silicon nitride layer is 18nm, and the refractive index is 2.07%; finally, SiH4 and NH3 are introduced at flow rates of 1500sccm / min and 15000sccm / min, respectively, and the reaction time is 280s, to deposit a third silicon nitride layer, the film thickness of the third silicon nitride layer is 22nm, and the refractive index is 2.00%;

[0090] Two layers of silicon oxynitride were deposited on the front side. Under the condition of depositing three layers of silicon nitride, reaction gases with flow ratios of SiH4:NH3:N2O=1100:5000:7000sccm / min and SiH4:NH3:N2O=900:4000:9000sccm / min were introduced in sequence. Under the RF power of 18kw, the film formation time was 130s for both times, and two layers of silicon oxynitride films with a film thickness of 9nm were deposited on the surface of the battery in sequence.

[0091] A layer of silicon oxide is deposited on the front side. Under the condition of depositing two layers of silicon nitride oxide, a reaction gas with a flow ratio of NH3:N2O=1000:13000sccm / min is introduced. At an RF power of 18kw, a layer of silicon oxide film with a refractive index of 1.9% and a film thickness of 6mm is deposited on the surface of the battery. The reaction time is 100s.

[0092] Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, use a tubular plasma vapor deposition machine, place the sheet on the graphite boat, and send it to the furnace tube by the paddle, evacuate, and anneal at a temperature of 550°C for 1000s; pull the furnace tube out under continuous vacuum / vacuum state, the reaction temperature is 550°C, the RF power of the first film is 15kw, and the reaction gas with a flow ratio of SiH4:NH3=3000:10000sccm / min is introduced. The reaction time is 160s, and a first silicon nitride layer with a refractive index of 2.5% and a film thickness of 20mm is deposited on the surface of the battery; Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, use a tubular plasma vapor deposition machine, and send the sheet on the graphite boat by the paddle, evacuate, and anneal at a temperature of 550°C for 1000s; pull the furnace tube out under continuous vacuum / vacuum state, the reaction temperature is 550°C, the RF power of the first film is 15kw, and the reaction gas with a flow ratio of SiH4:NH3=3000:10000sccm / min is introduced. The reaction time is 160s, and a first silicon nitride layer with a refractive index of 2.5% and a film thickness of 20mm is deposited on the surface of the battery; Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, and use a tubular plasma vapor deposition machine, and send the sheet on the back of the silicon substrate. The RF power of the second film is 16kw, the flow ratio of the reaction gas is SiH4:NH3=2000:13000sccm / min, the reaction time is 200s, and a second silicon nitride layer with a refractive index of 2.2% and a film thickness of 24mm is deposited on the surface of the battery; the RF power of the third film is 16kw, the flow ratio of the reaction gas is SiH4:NH3=1500:15000sccm / min, the reaction time is 260s, and a third silicon nitride layer with a refractive index of 2.0% and a film thickness of 20mm is deposited on the surface of the battery.

[0093] Step eight, screen printing, electrode printing and high-temperature sintering are performed on the front and back sides of the silicon substrate in sequence to form a good ohmic contact and obtain a front metal electrode and a back metal electrode.

[0094] Embodiment 4:

[0095] In this embodiment, a method for preparing a TOPCon cell with reduced UV attenuation includes the following steps:

[0096] Step 1: Perform double-sided texturing on the silicon substrate to obtain a textured silicon wafer, then diffuse boron ions on the front side of the textured silicon wafer to form a P+ doped layer and the borosilicate glass layer, then remove the borosilicate glass layer by etching, and polish the back surface of the silicon substrate with alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process.

[0097] Step 2: Prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the processed silicon substrate using an LPCVD process.

[0098] Step three, using POCl3 as a diffusion source, perform back side phosphorus diffusion to form a doped polysilicon layer.

[0099] Step 4: Use RCA to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove PSG and remove the edge and front PSG.

[0100] Step five, deposit an aluminum oxide passivation layer on the front side, using a chamber-type vapor phase molecular deposition machine, with a robot arm, lower the silicon wafer into the groove of the aluminum boat, insert a paddle and place it in the furnace tube, close the furnace door and start the dry pump to evacuate, when the temperature in the chamber is 260°C, introduce 45°C water vapor for 11 seconds, form a hydroxyl layer on the front surface of the silicon body, nitrogen purge for 10 seconds, then introduce 45°C tribasic aluminum vapor, nitrogen purge for 10 seconds, repeat the above cycle 35 times, and form a 6nm aluminum oxide passivation layer on the front surface.

[0101] Step 6: deposit three layers of silicon nitride on the front side, using a tubular plasma vapor deposition machine, after placing the sheet on the graphite boat, the paddle is sent to the furnace tube, evacuated, and annealed at a temperature of 560°C for 1800s; the furnace tube is leaked under the continuous vacuum breaking / vacuuming state, and when the temperature is stabilized at 560°C, SiH4 and NH3 are introduced at a flow rate of 2280sccm / min and 9570sccm / min respectively at a radio frequency power of 16kw, and the reaction time is 150s to deposit the first silicon nitride layer, and the film thickness of the first silicon nitride layer is 18nm. The refractive index is 2.2%; then SiH4 and NH3 are introduced at flow rates of 1800sccm / min and 12600sccm / min, respectively, and the reaction time is 150s, respectively, to deposit a second silicon nitride layer, the film thickness of the second silicon nitride layer is 16nm, and the refractive index is 2.07%; finally, SiH4 and NH3 are introduced at flow rates of 1200sccm / min and 12000sccm / min, respectively, and the reaction time is 250s, to deposit a third silicon nitride layer, the film thickness of the third silicon nitride layer is 20nm, and the refractive index is 2%;

[0102] Two layers of silicon oxynitride were deposited on the front side. Under the condition of depositing three layers of silicon nitride, reaction gases with flow ratios of SiH4:NH3:N2O=1100:4900:6700sccm / min and SiH4:NH3:N2O=810:3600:8010sccm / min were introduced in sequence. Under the RF power of 16kw, the film formation time was 120s for both times, and two layers of silicon oxynitride films with a thickness of 7nm were deposited on the surface of the battery in sequence.

[0103] A layer of silicon oxide is deposited on the front side. Under the condition of depositing two layers of silicon nitride oxide, a reaction gas with a flow ratio of NH3:N2O=900:11700sccm / min is introduced. At an RF power of 16kw, a layer of silicon oxide film with a refractive index of 1.7% and a film thickness of 5mm is deposited on the surface of the battery. The reaction time is 90s.

[0104] Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, use a tubular plasma vapor deposition machine, after the graphite boat is placed, it is sent to the furnace tube by the paddle, evacuated, and annealed at a temperature of 550°C for 900s; the furnace tube is leaked under the continuous vacuum breaking / vacuuming state, the reaction temperature is 550°C, the RF power of the first film is 13kw, the flow ratio of SiH4:NH3=2600:9400sccm / min of the reaction gas is introduced, the reaction time is 130s, and a first silicon nitride layer with a refractive index of 2.3% and a film thickness of 19mm is deposited on the surface of the battery; the second The RF power of the first film is 15kw, the flow rate ratio of the reaction gas is SiH4:NH3=1850:12500sccm / min, the reaction time is 180s, and a second silicon nitride layer with a refractive index of 2.1% and a film thickness of 22mm is deposited on the surface of the battery; the RF power of the third film is 15kw, the flow rate ratio of the reaction gas is SiH4:NH3=1400:14000sccm / min, the reaction time is 230s, and a third silicon nitride layer with a refractive index of 1.9% and a film thickness of 19mm is deposited on the surface of the battery.

[0105] Step eight, screen printing, electrode printing and high-temperature sintering are performed on the front and back sides of the silicon substrate in sequence to form a good ohmic contact and obtain a front metal electrode and a back metal electrode.

[0106] Embodiment 5:

[0107] In this embodiment, a method for preparing a TOPCon cell with reduced UV attenuation includes the following steps:

[0108] Step 1: Perform double-sided texturing on the silicon substrate to obtain a textured silicon wafer, then diffuse boron ions on the front side of the textured silicon wafer to form a P+ doped layer and the borosilicate glass layer, then remove the borosilicate glass layer by etching, and polish the back surface of the silicon substrate with alkali polishing to remove the phosphosilicate glass layer formed during the boron diffusion process.

[0109] Step 2: Prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the processed silicon substrate using an LPCVD process.

[0110] Step three, using POCl3 as a diffusion source, perform back side phosphorus diffusion to form a doped polysilicon layer.

[0111] Step 4: Use RCA to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; then remove PSG and remove the edge and front PSG.

[0112] Step five, deposit an aluminum oxide passivation layer on the front side, using a chamber-type vapor phase molecular deposition machine, with a robot arm, lower the silicon wafer into the groove of the aluminum boat, insert a paddle and place it in the furnace tube, close the furnace door and start the dry pump to evacuate, when the temperature in the chamber is 280°C, introduce 45°C water vapor for 12 seconds, form a hydroxyl layer on the front surface of the silicon body, nitrogen purge for 10 seconds, then introduce 45°C tribasic aluminum vapor, nitrogen purge for 10 seconds, repeat the above cycle 36 times, and form a 7nm aluminum oxide passivation layer on the front surface.

[0113] Step 6: deposit three layers of silicon nitride on the front side, using a tubular plasma vapor deposition machine, after placing the sheet on the graphite boat, the paddle is sent to the furnace tube, evacuated, and annealed at a temperature of 560°C for 1800s; the furnace tube is leaked under the continuous vacuum breaking / vacuuming state, and when the temperature is stabilized at 560°C, SiH4 and NH3 are introduced at a flow rate of 2280sccm / min and 9570sccm / min respectively at a radio frequency power of 16kw, and the reaction time is 150s to deposit the first silicon nitride layer, and the film thickness of the first silicon nitride layer is 18nm. The refractive index is 2.2%; then SiH4 and NH3 are introduced at flow rates of 1800sccm / min and 12600sccm / min, respectively, and the reaction time is 150s, respectively, to deposit a second silicon nitride layer, the film thickness of the second silicon nitride layer is 16nm, and the refractive index is 2.07%; finally, SiH4 and NH3 are introduced at flow rates of 1200sccm / min and 12000sccm / min, respectively, and the reaction time is 250s, to deposit a third silicon nitride layer, the film thickness of the third silicon nitride layer is 20nm, and the refractive index is 2%;

[0114] Two layers of silicon oxynitride were deposited on the front side. Under the condition of depositing three layers of silicon nitride, reaction gases with flow ratios of SiH4:NH3:N2O=1100:4900:6700sccm / min and SiH4:NH3:N2O=810:3600:8010sccm / min were introduced in sequence. Under the RF power of 16kw, the film formation time was 120s for both times, and two layers of silicon oxynitride films with a thickness of 7nm were deposited on the surface of the battery in sequence.

[0115] A layer of silicon oxide is deposited on the front side. Under the condition of depositing two layers of silicon nitride oxide, a reaction gas with a flow ratio of NH3:N2O=900:11700sccm / min is introduced. At an RF power of 16kw, a layer of silicon oxide film with a refractive index of 1.7% and a film thickness of 5mm is deposited on the surface of the battery. The reaction time is 90s.

[0116] Step seven, deposit three layers of silicon nitride on the back of the silicon substrate, use a tubular plasma vapor deposition machine, after the graphite boat is placed, it is sent to the furnace tube by the paddle, evacuated, and annealed at a temperature of 550°C for 900s; the furnace tube is leaked under the continuous vacuum breaking / vacuuming state, the reaction temperature is 550°C, the RF power of the first film is 13kw, the flow ratio of SiH4:NH3=2600:9400sccm / min of the reaction gas is introduced, the reaction time is 130s, and a first silicon nitride layer with a refractive index of 2.3% and a film thickness of 19mm is deposited on the surface of the battery; the second The RF power of the first film is 15kw, the flow rate ratio of the reaction gas is SiH4:NH3=1850:12500sccm / min, the reaction time is 180s, and a second silicon nitride layer with a refractive index of 2.1% and a film thickness of 22mm is deposited on the surface of the battery; the RF power of the third film is 15kw, the flow rate ratio of the reaction gas is SiH4:NH3=1400:14000sccm / min, the reaction time is 230s, and a third silicon nitride layer with a refractive index of 1.9% and a film thickness of 19mm is deposited on the surface of the battery.

[0117] Step eight, screen printing, electrode printing and high-temperature sintering are performed on the front and back sides of the silicon substrate in sequence to form a good ohmic contact and obtain a front metal electrode and a back metal electrode.

[0118] Comparative Example 1:

[0119] The preparation method in this comparative example 1 is the same as that in Example 2 except that only three silicon nitride layers are deposited on the front surface of the silicon substrate in step 6.

[0120] Comparative Example 2:

[0121] The preparation method in this comparative example 2 is the same as that in Example 2 except that in step 6, only three silicon nitride layers / two silicon oxynitride layers are deposited on the front surface of the silicon substrate.

[0122] Comparative Example 3:

[0123] In the preparation method of this comparative example 3, except that in step 6, only three silicon nitride layers / one silicon oxynitride layer / one silicon oxide layer are deposited on the front surface of the silicon substrate, the other steps are the same as those in Example 2.

[0124] Comparative Example 4:

[0125] The preparation method in this comparative example 4 is the same as that in Example 2 except that in step 6, only four silicon nitride layers / one silicon oxynitride layer / one silicon oxide layer are deposited on the front surface of the silicon substrate.

[0126] Comparative Example 5:

[0127] The preparation method in this comparative example 5 is the same as that in Example 2 except that in step 6, only three silicon nitride layers and one silicon oxide layer are deposited on the front surface of the silicon substrate.

[0128] The TOPCon solar cells obtained in the above five groups of embodiments and comparative examples were subjected to performance tests, and the results are as follows:

[0129] Table 1 TOPCon solar cell performance test results of Examples 1 to 5 and Comparative Examples 1 to 5

[0130] Example Total refractive index UV30 attenuation value UV60 attenuation value Example 1 2.04 0.24% 0.80% Example 2 2.04 0.15% 0.52% Example 3 2.04 0.25% 0.87% Example 4 2.04 0.22% 0.67% Example 5 2.04 0.20% 0.60% Comparative Example 1 2.04 0.78% 1.33% Comparative Example 2 2.04 0.73% 1.49% Comparative Example 3 2.04 0.68% 1.35% Comparative Example 4 2.04 0.69% 1.49% Comparative Example 5 2.04 0.69% 1.42%

[0131] It can be seen from Table 1 that the TOPCon solar cells prepared in Examples 1 to 5 of the present application can reduce the UV60 attenuation value to less than 1% by using three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer as the front anti-reflection layer, compared with their comparative examples 1 to 5 respectively.

[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a TOPCon cell with reduced UV attenuation, characterized in that: The steps include: Step 1: Clean and texturize the silicon substrate, diffuse boron on the front side, and perform etching and alkaline polishing treatment in sequence; Step 2, using LPCVD process to prepare a tunnel oxide layer and an intrinsic polysilicon layer on the back side of the treated silicon substrate; Step 3, using POCl3 as a diffusion source, performing back side phosphorus diffusion to form a doped polysilicon layer; Step 4: RCA is used to clean the back oxide layer, the N+ layer generated on the front and edge during the back phosphorus diffusion, and remove the front BSG; Then go to PSG, remove the edge and front PSG; Step 5, performing aluminum oxide atomic layer deposition on the front side of the silicon substrate to form an aluminum oxide passivation layer; Step 6: depositing three silicon nitride layers, two silicon oxynitride layers, and one silicon oxide layer on the front side of the silicon substrate in sequence to form a front anti-reflection layer; Step 7, depositing three silicon nitride layers on the back side of the silicon substrate to form a back side anti-reflection layer; Step eight, screen printing and electrode printing are performed on the front and back sides in turn, and high-temperature sintering is performed to form a good ohmic contact to obtain a front metal electrode and a back metal electrode.

2. The method for preparing a TOPCon solar cell according to claim 1, characterized in that: In the step six, three silicon nitride layers are deposited on the front side. First, SiH4 and NH3 are introduced at flow rates of 2000-3000sccm / min and 9000-10000sccm / min, respectively, and the reaction time is 120-180s to deposit the first silicon nitride layer; then SiH4 and NH3 are introduced at flow rates of 1600-2000sccm / min and 11000-14000sccm / min, respectively, and the reaction time is 120-180s to deposit the second silicon nitride layer; finally, SiH4 and NH3 are introduced at flow rates of 1000-1500sccm / min and 10000-15000sccm / min, respectively, and the reaction time is 220-280s to deposit the third silicon nitride layer.

3. The method for preparing a TOPCon solar cell according to claim 2, characterized in that: The first silicon nitride layer has a thickness of 16 to 20 nm and a refractive index of 2.10 to 2.30%; The second silicon nitride layer has a thickness of 14 to 18 nm and a refractive index of 2.00 to 2.07%; The third silicon nitride layer has a thickness of 18 to 22 nm and a refractive index of 1.80 to 2.00%.

4. The method for preparing a TOPCon solar cell according to claim 1, characterized in that: In the step six, two layers of silicon oxynitride are deposited on the front side, and reaction gases with flow ratios of SiH4:NH3:N2O=(1000-1100):(4000-5000):(6000-7000)sccm / min and SiH4:NH3:N2O=(800-900):(3000-4000):(8000-9000)sccm / min are introduced in sequence. The reaction time is 110-130s, and two layers of silicon oxynitride films with a thickness of 5-9nm are deposited in sequence on the surface of the battery.

5. The method for preparing a TOPCon solar cell according to claim 1, characterized in that: In step six, a silicon oxide layer is deposited on the front side, and a reaction gas with a flow ratio of NH3:N2O=(800-1000):(10000-13000)sccm / min is introduced. The reaction time is 80-100s, and a silicon oxide film with a refractive index of 1.5-1.9% and a film thickness of 4-6mm is deposited on the surface of the battery.

6. The method for preparing a TOPCon solar cell according to claim 1, characterized in that: In the step 7, three silicon nitride layers are deposited on the back side. First, a reaction gas with a flow rate ratio of SiH4:NH3=(2000-3000):(9000-10000)sccm / min is introduced, and the reaction time is 100-160s. Then, a first silicon nitride layer with a refractive index of 2.1-2.5% and a film thickness of 18-20mm is deposited on the surface of the battery; then, a reaction gas with a flow rate ratio of SiH4:NH3=(1000-2000):(12000-13000)sccm / m in reaction gas, the reaction time is 160 to 200 s, and a second silicon nitride layer with a refractive index of 2.0 to 2.2% and a film thickness of 20 to 24 mm is deposited on the surface of the battery; finally, a reaction gas with a flow rate ratio of SiH4:NH3=(1300 to 1500):(13000 to 15000) sccm / min is introduced, the reaction time is 200 to 260 s, and a third silicon nitride layer with a refractive index of 1.8 to 2.0% and a film thickness of 18 to 20 mm is deposited on the surface of the battery.

7. The method for preparing a TOPCon solar cell according to claim 1, characterized in that: In the step 5, an aluminum oxide passivation layer is deposited on the front side. Under vacuum conditions, water vapor is introduced to form a hydroxyl layer on the front surface of the silicon body and the layer is purged with nitrogen. Then, tribasic aluminum vapor is introduced and the layer is purged with nitrogen. The above cycle is repeated 34 to 36 times to form a 5-7 nm aluminum oxide passivation layer on the front side.

8. A TOPCon solar cell, characterized in that: The method is prepared by the method according to any one of claims 1 to 7.

9. The TOPCon solar cell according to claim 8, characterized in that: The silicon wafer comprises a P+ diffusion layer, an aluminum oxide passivation layer, a front anti-reflection layer and a front metal electrode, which are sequentially arranged on the front side of the silicon wafer, and a tunneling oxide layer, a doped polysilicon layer, a back anti-reflection layer and a back metal electrode, which are sequentially arranged on the back side of the silicon wafer; The front metal electrode penetrates the front anti-reflection layer, the aluminum oxide passivation layer and the P+ diffusion layer to form an ohmic contact; the back metal electrode penetrates the back anti-reflection layer and the doped polysilicon layer to form an ohmic contact.

10. The TOPCon solar cell according to claim 9, characterized in that: The front anti-reflection layer is the three silicon nitride layers / two silicon oxynitride layers / one silicon oxide layer; and the back anti-reflection layer is the three silicon nitride layers.

Citation Information

Patent Citations

  • Novel TOPCon solar cell and manufacturing method thereof

    CN115548135A

  • Front antireflection film structure of TOPCon battery and preparation method of front antireflection film structure

    CN116314355A

  • Preparation method of Topcon battery

    CN117525211A

Cited By

  • BC battery for improving UV attenuation and preparation method thereof

    CN120417529A

  • TOPCon solar cell and preparation method and application thereof

    CN120603353A

  • TOPCon battery preparation method for improving UVID and TOPCon battery

    CN121568469A

  • Anti-UVID anti-reflection passivation film and preparation method thereof

    CN121793516A